PENERAPAN TERAPI MUSIK KLASIK PADA PASIEN GANGGUAN PERSEPSI SENSORI : HALUSINASI PENDENGARAN DI RUANG YUDISTIRA RUMAH SAKIT JIWA DAERAH PROVINSI JAMBI - Purba, Hani Fransiska; Nasution, Riska Amalya; Mawarti, Indah; Yuliana, Yuliana (SEKOLAH TINGGI ILMU KESEHATAN INDRAMAYU, 2024)
According to Riskesdas (2018), as many as 400,000 people or around 1.7% are affected by schizophrenia in Indonesia. Schizophrenia is a chronic mental disorder that occurs in brain function causing changes in irregular thought patterns, delusions, inappropriate behavior changes, changes in psychosocial function and hallucinations, 70% of patients experience auditory hallucinations. Efforts that nurses can make to control patient hallucinations non-pharmacologically include classical music therapy which can improve a person's memory, concentration and perception. The design of this scientific paper uses a case report design with a nursing process approach. The subjects in this case study are patients with sensory perception disorders: auditory hallucinations who are being treated at the Jambi Province Regional Mental Hospital. Data analysis was carried out using descriptive analysis by looking at signs of hallucinations from the first to the last day of implementation. The results of the 5-day case study showed that there was a decrease in signs of hallucinations from a score of 10 to a score of 2. After classical music therapy intervention, there was a decrease in signs of hallucinations and the patient was able to control his hallucinations.